A Blog – a Place of Expressing Yourself or rather Creating a Virtual Identity? - Adamski, Andrzej (Žurnalistikos tyrimai, 2011)
‘Writing a blog’ – these words pertain to the communicative situation which, since it raises a number of questions, is only seemingly simple. For instance, what is the difference between a blog and a traditional daily? What kind of relation exists between a blogger and a reader? And finally, does a blog represent the reflection of an author’s real identity; or maybe it is the network environment that makes a blogger create his or her new identity, very often a fake one? The author will attempt to answer the above questions in the present study.Keywords: blog, blogger, identity, genre, reader, representation, traditional diary, virtual reality.